Exploring child health risks of poultry keeping in Ethiopia: Insights from the 2015 Feed the Future Survey - Headey, Derek D.; Hirvonen, Kalle (International Food Policy Research Institute, 2015)
The agricultural sector in Ethiopia and in other developing countries is increasingly asked to contribute to reducing undernutrition as well as poverty and food insecurity. Within agriculture, the livestock sector is thought to play a particularly important role in this respect, since the consumption of animal-sourced foods (ASFs) is a well-known determinant of child growth and the production of ASFs is an important source of income. However, there is growing evidence of associated health risks of poultry rearing in developing countries, particularly for young children who have been observed to directly ingest poultry feces. This is hypothesized to contribute to chronic gut damage – a condition termed environmental enteric disorder (EED) – that is widely believed to be a leading cause of child stunting in developing countries such as Ethiopia.